Analysis the Role of Management for Achieving of Public Health Coverage Programs at Public Health Care in Bengkulu (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Public Health Care is a primary public health service center. It is also as a promotive andpreventive service provider with a target group and community to maintain and improve health and preventdisease. In the implementation of the health program the management function in the public health center iscalled planning (P), Mobilizing implementation (MI), Supervision Control Assessment (SCA). The purposeof conducting a public health care management analysis is Planning (P), Mobilizing Implementation (M.I),and Supervision Control Assessment (SCA) on the achievement of public health care performance indicatorsin Bengkulu City. Study Design: The research design used is exploratory or non-experinmental research for qualitativemethods and analytic research designs are cross sectional observational approaches for quantitativemethods with hypothesis testing. Informants in this qualitative study were carried out by means of purposivesampling, namely by conducting interviews with all the Head of Public Health Center. The sample in thisstudy amounted to 80 samples consisting of the head of the Public Health Center, the person in charge of theprogram and the implementer of the Public health care program/activityResults: There is a relationship between Management functions (planning, mobilizing implementation,controlling assessment control) to the achievement of the performance of the Environmental Health,Nutrition, Prevention and Disease Control program at Bengkulu City Health Center;Conclusion: The implementation of management functions (Planning, Mobilizing Implementation,Supervision Control Assessment) influences the Environmental Health, Nutrition, Disease Prevention andControl program in Bengkulu City Health center.